Cilia-related gene signature in the nasal mucosa correlates with disease severity and outcomes in critical respiratory syncytial virus bronchiolitis - Koch, Clarissa M.; Prigge, Andrew D.; Setar, Leah; Anekalla, Kishore R.; Do-Umehara, Hahn Chi; Abdala-Valencia, Hiam; Politanska, Yuliya; Shukla, Avani; Chavez, Jairo; Hahn, Grant R.; Coates, Bria M. (Frontiers in Immunology, 2022)
Background Respiratory syncytial virus (RSV) can cause life-threatening respiratory failure in infants. We sought to characterize the local host response to RSV infection in the nasal mucosa of infants with critical bronchiolitis and to identify early admission gene signatures associated with clinical outcomes. Methods Nasal scrape biopsies were obtained from 33 infants admitted to the pediatric intensive care unit (PICU) with critical RSV bronchiolitis requiring non-invasive respiratory support (NIS) or invasive mechanical ventilation (IMV), and RNA sequencing (RNA-seq) was performed. Gene expression in participants who required shortened NIS ( 3 days), and IMV was compared. Findings Increased expression of ciliated cell genes and estimated ciliated cell abundance, but not immune cell abundance, positively correlated with duration of hospitalization in infants with critical bronchiolitis. A ciliated cell signature characterized infants who required NIS for > 3 days while a basal cell signature was present in infants who required NIS for